PREVALENCE OF LOWER CROSS SYNDROME IN BANK EMPLOYEES - Oswal, Sakshi Champaklal; Shinde, Sandeep (International Journal of Psychosocial Rehabilitation, 2020)
Background: Bank Employees have sedentary lifestyle, 8-10hrs of sitting. Due to tightness and weakness in lower body muscle, muscle imbalance is common in these subjects. The purpose of this study was to find the prevalence of Lower Cross Syndrome(LCS) and average number of bank employees who are at risk of developing LCS. 98 Bank Employees of age group 30-40 years having 8-10hrs of sitting both male and female, subject were all of karad considering all exclusion criteria were selected. After taking the consent procedure was explained to the subjects. The subjects were explained the testing position and asked to assume the same. Tests for checking the muscle weakness and musclemuscle tightness of Gluteals and Abdominal muscles using Manual Muscle Testing(MMT) were performed and Thomas Test was used for testing tightness of hip flexor muscle and postural assessment was taken. Statistical analysis of MMT and Thomas test were found to be extremely significant with a P value of